Innovation of Tourism Products in Increasing Sales of Lipa Sabbe Sengkang to Entrepreneurs in Wajo Regency - Andi Abriani (Borong Newinera Publisher, 2023)
This study aims to determine the Increase in Sales Volume of Lipa Sabbe Sengkang Tourism Products and the Increase in Volume of Lipa Sabbe Sengkang Tourism Products in Wajo Regency. The type of research uses qualitative methods, namely the presentation of data in the form of statements of words or descriptions of something in the form of sentences set forth in writing. The data collection techniques use observation, interviews, and documentation. The results of this study showed that tourism product innovation in increasing sales volume of Lipa Sabbe Sengkang to entrepreneurs in Wajo district. The researcher added that entrepreneurs should hold promotions more often so that tourists are aware of new production, the existence of Lipa Sabbe Sengkang, opportunities that can be implemented well if entrepreneurs work together to carry out marketing and promotion, the Government and the public really need to get to know Lipa Sabbe Sengkang closely. In increasing sales of Lipa Sabbe Sengkang Tourism Products to market Lipa Sabbe Sengkang Tourism Products so that Entrepreneurs take various events to promote to Social Media and introduce globally including holding a Silk Festival in Wajo Regency because Lipa Sabbe Sengkang is a Cultural Identity for the city of Sengkang, Wajo Regency.